SMALL CLAIM COURT PROCEDURES IN UPHOLDING THE PRINCIPLES OF SIMPLE, FAST, AND LOW COST COURTS IN INDONESIAN CIVIL PROCEDURE LAW - Hariwijaya, Ramadian Putra; Adnyana, I Gusti Ngurah (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2021)
This legal research aims to explore important aspects concerning the settlement of simple lawsuits and the legal considerations made by judges in establishing the settlement of such cases. The research adopts a Normative Juridical method, which involves analyzing issues through library research, summarizing and interpreting legal doctrine opinions. The conclusions drawn from the research and discussions are as follows: Firstly, there are specific requirements for settling simple lawsuits that differ from those of regular civil proceedings. The time period and value of the object involved in simple lawsuits are distinct from ordinary civil lawsuits. Secondly, in determining the settlement of a simple claim, judges carefully consider the evidence presented by the Plaintiff, including documentary evidence and credible witnesses, ensuring that the lawsuit satisfies the elements outlined in PERMA number 4 of 2019.